Soil Chemical Properties of Silver Fir and Spruce forests under Different Systems of Silviculture. - Gupta, M. K.; Jha, M. N.; Singh, R. P. (Indian Forester, 1990)
To study the effects of different management practices I e. selection, shelterwood and clearfelled on the status of soil potassium (total and available). An investigation has been carried out in silver fir (Abies pindrow) and spruce (Picea smithicna) forest of Narkada under Kumarsein Forest Range of H.P. Soils of this region were found sufficently rich in soil potassium contents with specific effects of management systems and site conditions clearly marked. Soil potassium decreased with increasing soil depth in all sites and management systems Intercorrelation between total and available potassium form was observed to be significantly positive. Soils of selection management system showed higher content of soil potassium followed by shelterwood and clearfelled systems, Same trend was observed in good, average and poor sites.